2020
DOI: 10.3390/nu12030813
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Structured Nutrition Therapy for Ramadan with Standard Care in Type 2 Diabetes Patients

Abstract: 1) Background: Structured nutrition therapy (NT) is essential for the management of type 2 diabetes (T2D), but the optimal delivery during Ramadan fasting remains unclear. The present study aimed to evaluate the effect of structured NT program versus standard care in patients with T2D during Ramadan.(2) Methods: The present study was an 8-week, parallel, non-randomized study with patients' preference design involving 64 patients with T2D. The participants were asked to choose their preferred group, i.e., struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…An overall healthy eating plan that results in an energy deficit, in conjunction with medications and/or metabolic surgery as individually appropriate, should be considered to support glycaemic and weight management goals in adults with type 2 diabetes [ 5 , 22 ]. Structured nutrition and lifestyle programmes may be considered for glycaemic benefit and can be adapted for specific cultural indications [ 83 – 87 ].…”
Section: Therapeutic Options: Lifestyle and Healthy Behaviour Weight ...mentioning
confidence: 99%
“…An overall healthy eating plan that results in an energy deficit, in conjunction with medications and/or metabolic surgery as individually appropriate, should be considered to support glycaemic and weight management goals in adults with type 2 diabetes [ 5 , 22 ]. Structured nutrition and lifestyle programmes may be considered for glycaemic benefit and can be adapted for specific cultural indications [ 83 – 87 ].…”
Section: Therapeutic Options: Lifestyle and Healthy Behaviour Weight ...mentioning
confidence: 99%
“…This instrument has been used in numerous studies in both type I DM and type 2 DM patients. [ 167 ] 1 [ 168 ] SWAL-QOL Dysphagia SWAL-QOL, a disease-specific measure of quality of life and quality of care for patients with oropharyngeal dysphagia. It assesses 10 QoL concepts; eight of which are dysphagia-related QoL (food selection, burden, mental health, social functioning, fear, eating duration, eating desire, communication) and two pertaining to general QoL (sleep and fatigue).…”
Section: Resultsmentioning
confidence: 99%
“…Favorable questions (1-5) were scored as follows: 1 = strongly disagree, 2 = disagree, 3 = agree, and 4 = strongly agree. For unfavorable questions (6)(7)(8)(9)(10)(11)(12)(13), this scoring was reversed as follows: 1 = strongly agree, 2 = agree, 3 = disagree, and 4 = strongly disagree. The questionnaire was completed before the intervention (baseline T1) and at the end of the intervention (i.e., at the end of Ramadan fasting, T2).…”
Section: Assessment Of Adherence To Nutrition Educationmentioning
confidence: 99%
“…A number of classical prospective epidemiological studies have reported a constant relationship between high CRP levels and an increased possibility of cardiovascular episodes comprising myocardial infarction, stroke, and cardiovascular disease (CVD)related mortality (10)(11)(12)(13)(14). Other markers that are related to obesity and cardiovascular health include cytokines (pro-and antiinflammatory) and chemokines.…”
Section: Introductionmentioning
confidence: 99%